Mutation patterns and prognostic analysis of BRAF/KRAS/PIK3CA in colorectal cancer. Issue 6 (18th April 2022) - Wang, Chengfeng; Pan, Diling
Abstract: Background and objective: Aberrant gene expression and abnormal signaling pathways often occur in patients with colorectal cancer, in which mutations in B‐Raf Proto‐Oncogene (BRAF), KRAS Proto‐Oncogene (KRAS), and Phosphatidylinositol‐4, 5‐Bisphosphate 3‐Kinase Catalytic Subunit Alpha (PIK3CA) are quite common. In this study, the relationship between BRAF, KRAS, and PIK3CA mutations and clinicopathologic features and prognosis of colorectal cancer patients was investigated. Methods: One hundred and fifty patients with colorectal cancer admitted to Affiliated people's Hospital (Fujian Provincial People's Hospital), Fujian University of Traditional Chinese Medicine were collected and grouped according to the mutation patterns of BRAF, KRAS, and PIK3CA. The association between BRAF, KRAS, and PIK3CA mutations and pathological factors (age, sex, etc.) was analyzed using the Chi‐square test. Subsequently, survival analysis was performed to screen the impact factors of overall survival time by Kaplan–Meier (K‐M) curve, and Cox regression model was established for the selected factors. Results: BRAF, KRAS, and PIK3CA mutations were not associated with age, sex, and alcoholism. K–M curve and log‐rank test results demonstrated that among the factors included in this study, overall survival rate of colorectal cancer patients was only associated with mutation factors. The prognosis of KRAS+/PIK3CA−/BRAF−mutant and KRAS−/PIK3CA−/BRAF+mutant patients was better than that of KRAS+/PIK3CA+/BRAF−mutant patients. Conclusion: The mutant patterns of BRAF, KRAS, and PIK3CA were not related to the general and clinicopathological features of patients. The mutant pattern could be used as an independent prognostic factor for colorectal cancer.